Biosynthesis and regulatory mechanisms of anthocyanins in rapeseed (Brassica napus) - Hongyan Wang; Emily Nyangoma; Xiangyan He; Zhengfu Wang; Fuyong Zhao (Planta, 2026)

Indigenous beneficial microbes contribute to pathogen inhibition in Chinese yam continuously cropped soil - Huanhuan Cheng; Yifan Cao; Paidamoyo Mataranyika; Ziyi Yuan; Yan Wang; Jian Yang; Luqi Huang; Zongzhuan Shen; Qirong Shen; Rong Li (Applied Soil Ecology, 2026)

Seasonal responses of land surface temperature to landscape patterns and multi-objective optimization in urban–rural fringe: a case study of Changqing District of Jinan City, China - Min Wang; Zihan Li; Xiaoyu Wang; Zhongjian Shen; Jinyan Wang; Huanan Wan; Chang’an Zuo; Tianran Wang (Environmental Monitoring and Assessment, 2026)

Toxoplasma gondii infection reduces CD59 expression through downregulation of JAK2/STAT3 signaling axis to enhance decidual NK cell cytotoxicity via the RAS/MAPK pathway - Shuyan Wang; Luyun Huo; Yan Zou; Ruohan Yang; Xiao Wang; Haixia Zhang; Liqin Ren; Jing Yang; Jie Li; Xuemei Hu; Yushan Ren (Inflammation Research, 2026)

Toward Automated and Refined Rock Mass Quality Evaluation: An AR-RMR System Driven by AI and Multi-source Heterogeneous Data - Xiang Wu; Fengyan Wang; Jianping Chen; Mingchang Wang; Lina Cheng; Chengyao Zhang; Junke Xu; Qing Ding (Rock Mechanics and Rock Engineering, 2026)

Amino acid-chelated zinc application enhances sugar beet growth performance in carbonate alkaline soil by optimizing rhizosphere zinc speciation and microbial community structure - Jianyu Zhang; Chuanhe Zhao; Yunlong Guo; Muhammad Ishfaq; Songlin Yang; Wenya Wang; Qiue Jia; Shangxuan Liu; Yan Wang; Wang Xing; Baiquan Song (Applied Soil Ecology, 2026)

Intermittent aeration-driven iron cycling for the remediation of waste pit-sealing mud: metabolic mechanisms and model evaluation - Xiangshan Zeng; Xinyi Wu; Dandan Yan; Changhui Hu; Jinlai Yuan; Ruiqi Li; Yan Wang; Ming Dou; Yafei Yang (Environmental Geochemistry and Health, 2026)

Spatiotemporal distribution and habitat suitability of the anadromous fish Coilia nasus revealed by environmental DNA and MaxEnt modelling - Xia Yuan; Hongliang Zhang; Mengqi Mao; Yunhao Zhao; Yongdong Zhou; Kaida Xu; Rijin Jiang; Xiaoyan Wang (Fisheries Research, 2026)

Urbanization filters the nematode gut microbiome: deterministic assembly and network stabilization of the core microbiota - Shihui Kang; Xun Han; Junkai Pei; Yan Wang; Tao Zhou; Hongtao Wang; Fei Zheng (Applied Soil Ecology, 2026)

Microbial mechanisms driving soil CO2 emissions under long-term straw mulching and N fertilization in a wheat–maize rotation system - Pengfei Li; Yikai Zhao; Afeng Zhang; Hangyu Xiao; Zihan Shan; Yan Wang; Jialu Gong; Qaiser Hussain; Jianbin Zhou; Zhujun Chen; Xudong Wang (Applied Soil Ecology, 2026)

A fully Eulerian multiphysics model for pressure solution - Ziyan Wang (Advances in Water Resources, 2026)

Multi-omics analysis reveals the regulatory network of soil stoichiometry and rhizosphere microbiota on saikosaponins in Bupleurum chinense DC. - Yan Wang; Quan Guo; Chen Yang; Honghong Jiao; Xiaochen Hu; Feng Yan; Mingying Zhang; Gang Zhang; Yimin Li (Applied Soil Ecology, 2026)

Agricultural and socio-ecological benefits of reducing chemical nitrogen fertilizer and using organic amendments: a sugar beet case study in China's black soil region - Yunlong Guo; Xiaochen Lin; Muhammad Faheem Adil; Muhammad Ishfaq; Muhammad Riaz; Shafaque Sehar; Songlin Yang; Yan Wang; Zhishan Yan; Baiquan Song (Applied Soil Ecology, 2026)

Nitrogen thresholds for coastal Casuarina equisetifolia: Soil acidification and microbial shifts drive restoration limits - Wei Chu; Yue Guo; ZongNan Wu; YanYan Wang; MingMei Wu; ZeYan Wu; WenXiong Lin (Applied Soil Ecology, 2026)

Distinct nitrogen application strategies and straw incorporation modulate carbon mineralization rate and SOC dynamics by regulating soil microbiome composition - Muhammad Irfan; Yiliu Wang; Solomon Yokamo; Yifan Wang; Muhammad Ahmed Akram; Dianjun Lu; Xiaoqin Chen; Huoyan Wang (Applied Soil Ecology, 2025)

Bacterial communities driving cabbage yield increases and pathogenic risks reduces following wastewater irrigation: Effects of nitrification inhibitors on different soil-vegetable systems - Manyun Zhang; Minzhe Zhou; Xinlin Zhao; Shahla Hosseini Bai; Hua Wang; Bin Ma; Tangrong Zhou; Yan Wang; Zhenrong Huang; Benliang Zhao; Wenhui Tang; Falin Chen (Applied Soil Ecology, 2025)

The efficacy of Perilla frutescens rotation and Trichoderma harzianum application in mitigating continuous cropping challenges of Panax notoginseng - Yan WANG; Yingpin LIU; Guobing TIAN; Shengchao YANG; Junwen CHEN; Shuhui ZI; Wei FAN; Qiaoran MA; Jiamin LIU; Ping ZHAO; Shuran HE (Applied Soil Ecology, 2025)

Urbanization enhances soil nitrogen mineralization mainly by increasing particulate organic nitrogen fractions in urban park greenspaces: A case study in Hangzhou, China - Bo Fan; Yuye Shen; Yan Wang; Liming Yin; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Applied Soil Ecology, 2025)

The growth of submerged plant Potamogeton crispus L. affected complete ammonia oxidizers in the rhizosphere - Jianzhao Li; Ziqi Liu; Yan Wang; Naidong Xiao; Xiaoqiong Wan; Yumei Hua; Jianwei Zhao (Applied Soil Ecology, 2025)

Lithological impact on topsoil organic carbon storage of karst forest soils shaped by aggregate pool complexity and their molecular composition - Qingmei Lin; Shuotong Chen; Xiao Feng; Thammavongsa Sounilan; Kun Cheng; Xuhui Zhang; Rongjun Bian; Xiaoyu Liu; Yan Wang; Marios Drosos; Jufeng Zheng; Lianqing Li; et al. (Applied Soil Ecology, 2025)

Impacts of continuous potato cropping on soil microbial assembly processes and spread of potato common scab - Lichun Wang; Song Liu; Guokui Tian; Yang Pan; Haiyan Wang; Guangwei Qiu; Fengyun Li; Ze Pang; Kaixin Ding; Jinpeng Zhang; Hong Xue; Xinyuan Li; et al. (Applied Soil Ecology, 2025)

A deep learning upscaling framework: Reactive transport and mineral precipitation in fracture-matrix systems - Ziyan Wang; Ilenia Battiato (Advances in Water Resources, 2024)

An improved light use efficiency model by considering canopy nitrogen concentrations and multiple environmental factors - Helin Zhang; Jia Bai; Rui Sun; Yan Wang; Zhiqiang Xiao; Bowen Song (Agricultural and Forest Meteorology, 2023)

Metabolic reprogramming in crustaceans: A vital immune and environmental response strategy - Zhongyan Wang; Yueling Zhang; Defu Yao; Yongzhen Zhao; Ngoc Tuan Tran; Shengkang Li; Hongyu Ma; Jude Juventus Aweya (Reviews in Aquaculture, 2022)
Most host organisms undergo metabolic changes in response to pathogens, environmental cues or simply to boost their immunity. Metabolic modulation has therefore been exploited by both host and pathogens to outwit the other during host–pathogen interactions. Recent studies have revealed that a growing number of metabolites and metabolic processes in crustaceans are crucial in host–pathogen interactions. Here, we reviewed recent work on metabolic changes during immune response of crustaceans and the metabolic reprogramming that takes place in the host induced by pathogens, environmental cues or as a host strategy to withstand these changes or clear the pathogen. In aquaculture crustaceans, limited studies exist on this subject; hence, we will also highlight themes for possible future research on metabolite reprogramming and how this strategy can be leveraged to improve sustainable aquaculture and enhance crustaceans’ response to pathogens and environmental changes.

A comprehensive review on genetically modified fish: key techniques, applications and future prospects - Yan Wang; Naima Hamid; Pan‐Pan Jia; De‐Sheng Pei (Reviews in Aquaculture, 2021)
Genetically modified fish is a general term used for whole fish whose DNA has been artificially altered by directly integrating (or deleting) single or multiple genes to introduce or modify a targeted character. Different techniques have been performed to produce genetically modified fish. Importantly, the introduction of various types of fluorescent proteins has dramatically expanded the range of applications of genetically modified fish. Currently, genetically modified fish have been widely employed as experimental models for medical science, pharmacology and environmental toxicology. The commercial application of genetically modified fish in aquaculture is still up for debate, although the first commercialization of genetically modified fish, GloFish, was in 2003, and further, the United States and Canada approved the commercial production and sale of the AquAdvantage Salmon. In this review, we discuss the principles and developmental history of fish transgenesis via gene transfer and gene‐editing techniques, and their applications in diverse fields. Further, challenges and prospects associated with the genetically modified fish are discussed.